CFD and Wind Tunnel Analysis for Mounted-Wind Turbine in a Tall Building for Power Generation - Dany Perwita Sari; Kang-Pyo Cho (National Research and Innovation Agency, 2014)
A mounted wind turbine on the top of a tall building may provide high wind power in regions of high wind speed and low turbulence. The objective of this study is to evaluate wind speed on roof top models to optimize the wind turbine performance for power generation. Comparative analyses from three different roof top models were conducted. Computational Fluid Dynamics (CFD) simulation and wind tunnel testing were performed to evaluate the performance of wind turbine. Wind speed on the building model with a geometric scale of 1:150 was measured in CFD simulation then it was validated in wind tunnel test. Results presented in this paper suggest that an increase of wind speed could be achieved with ¼ circular shapes around the rooftop which can provide additional wind speed of 55.24%, respectively.